2020
DOI: 10.12688/f1000research.22274.2
|View full text |Cite
|
Sign up to set email alerts
|

First derivative ATR-FTIR spectroscopic method as a green tool for the quantitative determination of diclofenac sodium tablets

Abstract: Background: Attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy is a rapid quantitative method which has been applied for pharmaceutical analysis. This work describes the utility of first derivative ATR-FTIR spectroscopy in the quantitative determination of diclofenac sodium tablets. Methods: This analytical quantitative technique depends on a first derivative measurement of the area of infrared bands corresponding to the CO stretching range of 1550-1605 cm-1. The specificity, linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The function provided the basic tool that allows the spectrometer resolution to be tuned to the degree required to greatly enhance the band separation of each spectrum. 20 The average spectra of each group, and each sample separately, were calculated. The spectra of the controls were subtracted from the average cancer spectra in order to obtain an overview of the differences between the spectra of the study groups and to be able to choose the spectral bands that provided the most information and relevance for the statistical analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The function provided the basic tool that allows the spectrometer resolution to be tuned to the degree required to greatly enhance the band separation of each spectrum. 20 The average spectra of each group, and each sample separately, were calculated. The spectra of the controls were subtracted from the average cancer spectra in order to obtain an overview of the differences between the spectra of the study groups and to be able to choose the spectral bands that provided the most information and relevance for the statistical analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…First derivative spectra was calculated simply by taking the difference in absorbance between two closely spaced wavelengths for all wavelengths: where the derivative amplitude, D λ , was calculated for a wavelength intermediate between the two absorbance wavelengths. For the second-derivative determination three closely spaced wavelength values were used: The function provided the basic tool that allows the spectrometer resolution to be tuned to the degree required to greatly enhance the band separation of each spectrum …”
Section: Methodsmentioning
confidence: 99%
“…Many attempts were suggested for using derivative IR in determination diclofenac sodium in its formulations, but the results indicated that the first derivative spectra are the best technique for determination of diclofenac sodium. The first derivative spectra deleted IR band overlapping with the band understudies and increased sensitivity without any interference of the other band's [19].…”
Section: Quantitative Analysis Examplementioning
confidence: 99%
“…Maximum normalisation followed the smoothing step to achieve the same range (0-1) for the spectral data (Rinnan et al, 2009). Finally, the first derivative was applied to clarify the absorption bands and eliminate overlapping between neighbouring peaks (Fahelelbom et al, 2020).…”
Section: Soil Analyses and Spectral Measurementmentioning
confidence: 99%